LOS CYNEGETICA FRAGMENTARIOS Y EL FRACASO DEL CAZADOR - Martínez, Sebastián (Myrtia, 2000)
Fragments of Cynegetica and the failed hunter. This paper deals with several fragments attribued to supposed Cynegetica of Nicander of Colophon and Sostratus (or Sosicrates) Phanagorites.